Examining the relationship between pediatric nurses' liking of children levels and their codependency - Aylin Pekyiğit; Tuğba Yıldırım; Burcu Çalık Bağrıyanık (Tehran University of Medical Sciences, 2024)
Background & Aim: Codependency is a type of pathological relationship.  Pediatric nurses' liking of children may make them accept children more easily, but it may also lead to codependency. This study aims to examine the relationship between pediatric nurses' liking of children's levels and their codependency. Methods & Materials: This study is a descriptive correlational study. Data were collected online via Google Forms by exponential non-discriminative snowball sampling using the Demographic Form, the Barnett Liking of Children Scale (BLCS), and the Nurse Codependency Questionnaire (NCQ). The study was completed with 260 nurses. The Mann-Whitney U test, Kruskal-Wallis H test, and Spearman correlation were used to analyze the data. Results: In this study, the nurses' BLCS median score was 86 (78-93) and their NCQ median score was 72 (64-82). A significant but weak correlation was observed both between age and the BLCS score (r=0.132; p<0.05) and between the overall BLCS and NCQ scores (r= 0.182; p<0.05). Conclusion: In this study, it was determined that as nurses' level of liking children increased, their level of codependency decreased. The findings suggest a significant, albeit weak, correlation between these two variables. These results underscore the importance of further research to fully understand the implications of these relationships and their potential impact on the nursing profession.